Profile of Anaphylactic Reaction in Surabaya from January 2014 to May 2018 - Amalia Putri Uswatun Hasanah; Ari Baskoro; Pesta Parulian Maurid Edwar (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Anaphylactic reaction is systemic hypersensitivity reaction. It is type 1 hypersensitivity reaction. The incidence can be mild to severe due to the sudden release of mediators by effector cells. This research aimed to examine the prevalence of anaphylactic reaction in Dr. Soetomo General Hospital in January 2014 until May 2018.Methods: This study was a cross-sectional and retrospective study by assessing patients’ medical records and was analyzed descriptively.Results: 22 patients were identified as anaphylactic reaction. The prevalence of anaphylactic reaction from year to year cannot be identified surely because of underdiagnose and underreporting. The most common cause of anaphylactic reaction in Dr. Soetomo General Hsopital was drugs (50%). The most drugs were antibiotics (22.73%) and the most antibiotics were groups of penicillin (40%) and cephalosporin (40%). The most common clinical manifestation was skin-related (77.27%), which includes urticaria (4.55%), angioedem (27.27%), pruritus (27.27%) cold skin (0.09%), pallor (4.55%), and cyanosis (4.55%). Most patients became better (45.54%) after getting treatment from the doctor.Conclusion: The most common cause of anaphylactic reaction was drugs, the most drugs were antibiotics and the most antibiotics were groups of penicillin and cephalosporin. The most clinical manifestation was skin-related. Most of anaphylactic reaction’s patients became better after getting treatment from the doctor. Underdiagnose and underreporting are the problem often encountered in cases of anaphylactic reaction.